2011
DOI: 10.1007/s12011-011-9237-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Decreased DNA Repair in Peripheral Blood Mononuclear Cells in Individuals Exposed to Arsenic and Lead in a Mining Site

Abstract: The aim of this study was to evaluate DNA damage and the capacity for DNA repair in children exposed to arsenic and lead. During 2006, we studied a total of 85 healthy children (aged 4-11 years) who were residents of Villa de la Paz (community A), Matehuala (community B), and Soledad de Graciano Sanchez (community C) in San Luis Potosi, Mexico. The quantification of arsenic in urine (AsU) and lead in blood (PbB) was performed by atomic absorption spectrophotometry. The alkaline comet assay was used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 52 publications
4
28
0
1
Order By: Relevance
“…DNA damage has been detected in ovarian tissue in a dose-dependent manner [29]. Similarly higher extent of DNA fragmentation has also been reported in different communities of San Luis Potosi State [37] and in different schools of Mexico [36] located at different distances from arsenic smelter area.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…DNA damage has been detected in ovarian tissue in a dose-dependent manner [29]. Similarly higher extent of DNA fragmentation has also been reported in different communities of San Luis Potosi State [37] and in different schools of Mexico [36] located at different distances from arsenic smelter area.…”
Section: Discussionsupporting
confidence: 52%
“…In seven studies of human population of different arsenic contaminated areas, arsenic exposure ranged from 6 months to 18 years. Among which only in one study, the exposure time was not been reported [37]. In these seven studies significant increase has been reported in comet tail length and tail moment of exposed individuals compared to unexposed or less exposed individuals.…”
Section: Statistical Factsmentioning
confidence: 92%
See 1 more Smart Citation
“…One micromolar As is sufficient to interfere with the activity of adenosine diphosphate poly-ribose polymerase-1 (PARP-1), thereby increasing SSB and DSB fragmentation (Qin et al, 2008). Sampling of peripheral blood via venipuncture is the best way to evaluate the genotoxic effects of arsenic in exposed population in a minimally invasive way (Basu et al, 2005;Palus et al, 2005;Vuyyuri et al, 2006;Banerjee et al, 2008;Jasso-Pineda et al, 2012). The time of exposure to arsenic is an important parameter for determination of genotoxic damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that repair protein expression may be lowered following chronic exposure to arsenic [45,55]; however, this mode of action cannot explain the NER repair inhibition by arsenic observed in short-term studies mentioned above.…”
Section: Possible Mechanisms Of Ner Inhibition By Arsenic 41 Arsenicmentioning
confidence: 99%